De cabeça de porco à bebida de negro: um estudo sobre a produção e o consumo da aguardente nas Minas Gerais no século XVIII - Valquiria Ferreira da Silva (2015)
This dissertation investigates some aspects of the history of drinkes from sugarcane in Minas Gerais at eighteenth-century. To these drinks produced, which are constituent elements of the historical process of the mining captaincy, they were assigned aspects related to conflicts, disorders, waywardness while they were seen as essential components of social control and tax, fundamental nutritional diet and cure for various diseases, especially of the captives. The performances of the metropolitan and the colonists agents were analyzed in accordance with the law and the tax assessed to the production, circulation and consumption of alcoholic beverages in the region. Several document as cartas de sesmarias, requirementos para levantamentos de engenhos, orders, bandos, metropolitan representatives correspondences, manifestos das aguardente, autos de achadas, listas de almotaçarias, medical treated, inventories and wills were analyzed in order to understand the social place, assigned to these drinks from earth from these agents. Sought to realized also how the instrumentalization of designators assigned at this drinks derived from sugarcane - aguardente and cachaça - was able to order the daily life of that mining company eighteenth century. Finally, as conclusion, it was found that since the beginning of eighteenth century the production the drinks from sugarcane were found spread throughout the region of the mines in diversified production units with respect to size. Also it was noticed that these drinks could be obtained from the sugar production and brown sugar - molasses and the leftovers - or directly from the juice of the cane. In Addition, there was along the eighteenth century a gradual standardization of this production which now lead these drinks mainly from sugarcane juice, which, in other words were already indications of the importance that they would acquire in the region over the next centuries.